Bovine Viral Diarrhea Virus (BVDV): A Preliminary Study on Antiviral Properties of Some Aromatic and Medicinal Plants - Silvia Madeddu; Alessandra Marongiu; Giuseppina Sanna; Carla Zannella; Danilo Falconieri; Silvia Porcedda; Aldo Manzin; Alessandra Piras (Pathogens, 2021)
Plant products provide an alternative and successful source of lead compounds for the pharmaceutical industry. The present study was aimed to evaluate, in cell-based assays, the antiviral properties of essential oils obtained from plants that commonly grow in Sardinia, Italy, against a broad spectrum of RNA/DNA viruses. The essential oils of Helichrisumitalicum (Roth) G. Don ssp. microphyllum (Willd.) Nyman, Laurus nobilis L., Mirtuscommunis L., Pistacia lentiscus L., Salvia officinalis L., Saturejathymbra L., Lavandula angustifolia Mill., Foeniculum vulgare Mill., and Eucalyptus globulus Labill. were extracted by hydrodistillation and analyzed by gas chromatography mass spectrometry (GC–MS). Interestingly, the essential oil of Salvia officinalis showed moderate activity against bovine viral diarrhea virus (BVDV), an enveloped RNA virus belonging to the Flaviviridae family. BVDV is responsible for several clinical manifestations in bovines, including respiratory, gastroenteric, and reproductive diseases, with a significant economic impact. With the aim to individuate the constituent of the Salvia officinalis responsible for the biological activity, we tested the major components of the oil: camphene, β-pinene, limonene, 1,8-cineole, cis-thujone, camphor, (E)-caryophyllene, and α-humulene. Here, we describe α-humulene as an active component that is non-cytotoxic and active against BVDV (EC50 = 36 µM). Its antiviral effects were evaluated using virucidal cytopathic effect inhibition and viral yield reduction assays. This is the first scientific report showing the anti BVDV effects of Salvia officinalis essential oil and α-humulene as the main active component.